2016
DOI: 10.1097/mpa.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Pancrelipase/Pancreatin in Patients With Exocrine Pancreatic Insufficiency and a Medical History of Diabetes Mellitus

Abstract: Pancrelipase improved fat and protein absorption in patients with EPI due to chronic pancreatitis or pancreatectomy, with or without DM, and matched the safety profile previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
0
13
0
3
Order By: Relevance
“…Three small trials studied the efficacy of PERT in patients with diabetes mellitus secondary to chronic pancreatitis [90,91]. Treatment with PERT demonstrated a significant reduction in post-prandial plasma glucose and glycosylated hemoglobin at 6 months versus baseline values in patients with diabetes due to tropical calculous pancreatitis [92]. In contrast, PERT did not improve mean glucose values; it produced potentially life-threatening disturbances in glucose control among insulin-dependent diabetic patients due to chronic pancreatitis [93].…”
Section: Therapymentioning
confidence: 99%
“…Three small trials studied the efficacy of PERT in patients with diabetes mellitus secondary to chronic pancreatitis [90,91]. Treatment with PERT demonstrated a significant reduction in post-prandial plasma glucose and glycosylated hemoglobin at 6 months versus baseline values in patients with diabetes due to tropical calculous pancreatitis [92]. In contrast, PERT did not improve mean glucose values; it produced potentially life-threatening disturbances in glucose control among insulin-dependent diabetic patients due to chronic pancreatitis [93].…”
Section: Therapymentioning
confidence: 99%
“…2,3 CP may cause severe malnutritionand metabolic derangements if proper treatment is not provided. 48…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic enzyme replacement therapy (PERT) is widely used in the treatment of chronic pancreatitis patients exhibiting PEI-associated symptoms and improves fat and protein absorption and serum nutritional parameters in a significant population of these patients [3,4]. Recent clinical trials have shown that PERT results in relief and improvement of PEI-associated symptoms in patients with chronic pancreatitis [5].…”
Section: Introductionmentioning
confidence: 99%